Extent of Knowledge and Level of Adoption of Hobbyists in Ornamental Fish Keeping and Aquarium Management in Tripura - Laskar, Bonani; Saha, Biswarup; Sarkar, Atanu (International Journal of Bio-resource and Stress Management, 2016)
Aquarium fish keeping has been emerging as a popular hobby in Tripura. The study was conducted in the West Tripura district of Tripura in the year 2015–2016 among 100 randomly selected hobbyists of aquarium fish keeping. The data collected through observation and personal interview of the respondents revealed that majority of them were middle aged (36–50 years), all are literate and 50% of them were graduates. Around 39% of the hobbyists were businessmen. Further, the majority of the respondents (38%) were found to be spending ` 50–100 per month to manage their aquariums. Majority of the hobbyists (89%) liked to keep Gold fish (Carassius auratus) in their aquarium followed by keeping shark (Carchardon carcharias) and Koi carp like Milky carp and Malina carp (Cyprinus carpio). Small to medium sized aquariums between (2×1×1) ft to (3×1×1.5) ft were having highest preference. Around 69% of the hobbyists were having medium level of adoption score in different improved practices of ornamental fish keeping and aquarium management and the adoption index of the study area was 68.09. The variables like knowledge, education, information management behaviour and income were having significant positive relationship with adoption level. On the other hand, 67% of the respondents had medium extent of knowledge score. Gross majority of them (80%) flagged cleaning of tank to be their major issue whereas, 43% of them perceived that lack of scientific guidance regarding ornamental fish keeping and aquarium management was the major problem causing concern in continuing with the hobby.